A Collaborative Approach to Instructional Development - Heacock, Carolyn; Peixoto, Summer; Stamer-Peterson, Melissa; Šedriks, Baiba; Greene, Marina (Issues in Language Instruction, 2018)
Regardless of how long instructors have been in the classroom, they should continue to focus on improving their instructional practices. Being observed by others and observing others can inform teaching practices and assist in professional development. In the Applied English Center (AEC), the ESL center for the University of Kansas, formal observation by course coordinators is the primary instructional development tool used to provide instructors with targeted feedback about their teaching. However, because these formal observations are also evaluative in nature, they can create angst in instructors, making it difficult to view this tool as an opportunity to improve. Another tool instructors have used to improve their teaching is observing peers with the goal of seeing how colleagues approach their teaching. Those who have been able to observe their colleagues for this purpose have found this to be an effective (and less stressful) method for improving their own teaching; however, many instructors in the AEC have not had this opportunity to observe one another to learn from one another.